Canadian annual review of politics and public affairs. - Saywell, John T., 1929-2011 (Book collections on Project MUSE., 1974)
Featured in this edition are a review of the crucial Quebec provincial election in which the Parti quebecois went down to decisive defeat on a platform of independence, an overview of Canada's reponse to the Chilean coup, and an outline of government attempts to deal with the growing inflation and with the oil shortage.